Análisis del proceso productivo en la microempresa lácteos morales primer semestre 2016. Diseño de un modelo de gestión de trazabilidad - Morales Alban, Roberto Carlos (2017)
At present the methods, techniques and processes of food of animal origin as vegetable have been changing favorably towards the consumer, since the demand demands it well. All these changes have been positive to assure the safety and food safety when consuming, thus giving healthy populations and without causal diseases due to food or poor production practices. Traceability is the ability to track the movement of a food through all stages of production, processing and distribution, to ensure safety and quality throughout the supply chain. In Ecuador, the INEN ISO 22005: 2011 standard on food traceability governs. The traceability study was carried out in the microenterprise Lácteos Morales located in the Province of Cotopaxi, city Latacunga, Parish Tanicuchi. The traceability management model was designed to: 1. Know the sources of uncertainty in the market viability of products 2. Evaluate weights and inputs in the final quality of the product 3. Optimize the use of resources in processes through a model of traceability management 4. Reduce responsibility For the risks associated with the consumption of dairy products.